Influences of Breastfeeding Attitude, Subjective Norm, and Self-Efficacy on Intention to Exclusive Breastfeeding among Teenage Pregnant Women: อิทธิพลของทัศนคติ การคล้อยตามกลุ่มอ้างอิง และการรับรู้สมรรถนะแห่งตนต่อความตั้งใจในการเลี้ยงลูกด้วยนมแม่อย่างเดียวในสตรีตั้งครรภ์วัยรุ่น - Chansiri, Suphaphan; Phahuwatanakorn, Wanna; Yusamran, Chaweewan (Nursing Science Journal of Thailand, 2018)
Purpose: This study aimed to investigate the predictive power of breastfeeding attitude, subjective norm, and self-efficacy on intention to exclusive breastfeeding among teenage pregnant women. Design: Predictive correlational design. Methods: The sample consisted of 143 teenage pregnant women receiving antenatal care at one hospital in Chiang Rai province. Instruments included the Demographic Characteristics Interview, the Exclusive Breastfeeding Intention Interview, the Breastfeeding Attitude Questionnaire, the Breastfeeding Subjective Norm Questionnaire, and the Breastfeeding Self-Efficacy Scale-Short Form. Data were analyzed using descriptive statistics and Multiple Linear Regression. Main findings: The findings revealed that breastfeeding attitude, breastfeeding subjective norm, and self-efficacy were accounted for 29.2% of variance in exclusive breastfeeding among teenage pregnant women (R2 = .292, F = 19.070, p < .05). Breastfeeding subjective norm, and breastfeeding self-efficacy could predict intention to exclusive breastfeeding among teenage pregnant women with statistical significance (β = .463, .181, p < .05, respectively). Conclusion and recommendations: Breastfeeding subjective norm and self-efficacy affected intention to exclusive breastfeeding. Therefore, it is suggested that nurses and midwives should promote exclusive breastfeeding intention and have their mothers and husbands participate in breastfeeding as well as promote breastfeeding self-efficacy in teenage pregnant women. บทคัดย่อ วัตถุประสงค์: เพื่อศึกษาอำนาจการทำนายของทัศนคติในการเลี้ยงลูกด้วยนมแม่ การคล้อยตามกลุ่มอ้างอิง และการรับรู้สมรรถนะแห่งตนในการเลี้ยงลูกด้วยนมแม่ ต่อความตั้งใจในการเลี้ยงลูกด้วยนมแม่อย่างเดียวในสตรีตั้งครรภ์วัยรุ่น รูปแบบการวิจัย: การศึกษาความสัมพันธ์เชิงทำนาย วิธีดำเนินการวิจัย: กลุ่มตัวอย่างเป็นสตรีตั้งครรภ์วัยรุ่น จำนวน 143 คน ที่มาฝากครรภ์ ณ โรงพยาบาลแห่งหนึ่ง ในจังหวัดเชียงราย เก็บข้อมูลด้วยแบบสัมภาษณ์ข้อมูลส่วนบุคคล แบบสัมภาษณ์ความตั้งใจในการเลี้ยงลูกด้วยนมแม่อย่างเดียว แบบสอบถามทัศนคติในการเลี้ยงลูกด้วยนมแม่ แบบสอบถามการคล้อยตามกลุ่มอ้างอิงในการเลี้ยงลูกด้วยนมแม่ และแบบสอบถามการรับรู้สมรรถนะแห่งตนในการเลี้ยงลูกด้วยนมแม่ วิเคราะห์ข้อมูลโดยใช้สถิติพรรณนา และการถดถอยเชิงเส้นพหุคูณ ผลการวิจัย: ทัศนคติ การคล้อยตามกลุ่มอ้างอิง และการรับรู้สมรรถนะแห่งตน สามารถร่วมกันทำนายความตั้งใจในการเลี้ยงลูกด้วยนมแม่อย่างเดียวในสตรีตั้งครรภ์วัยรุ่นได้ร้อยละ 29.2 (R2 = .292, F = 19.070, p < .05) การคล้อยตามกลุ่มอ้างอิง และการรับรู้สมรรถนะแห่งตนสามารถทำนายความตั้งใจในการเลี้ยงลูกด้วยนมแม่อย่างเดียวในสตรีตั้งครรภ์วัยรุ่นได้อย่างมีนัยสำคัญทางสถิติ (β = .463, และ .181, p < .05 ตามลำดับ) สรุปและข้อเสนอแนะ: พยาบาลผดุงครรภ์ควรเสริมสร้างความตั้งใจในการเลี้ยงลูกด้วยนมแม่อย่างเดียวในสตรีตั้งครรภ์วัยรุ่น โดยให้แม่และสามี มีส่วนร่วม รวมทั้งส่งเสริมการรับรู้สมรรถนะแห่งตนในการเลี้ยงลูกด้วยนมแม่ในสตรีตั้งครรภ์วัยรุ่น